2018
DOI: 10.1097/aud.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning and Memory After Cochlear Implantation in Postlingually Deaf Adults: Some New Findings with the CVLT-II

Abstract: Results from this study suggest that several underlying foundational neurocognitive abilities are related to core speech perception outcomes after implantation in older adults. Implications of these findings for explaining individual differences and variability and predicting speech recognition outcomes after implantation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
78
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 61 publications
5
78
3
1
Order By: Relevance
“…Patients with MCI and dementia perform distinctly across these factors; thus, taking this performance into consideration could provide more accurate classification of cognitive function. A recent study tested the newly developed visual CVLT‐II protocol and found it comparable with the standard CVLT‐II protocol . This study also found overwhelming performance similarities on the visual CVLT‐II among a sample of experienced CI users and older NH adults with the exception of recency recall deficits, proactive interference, and forgetting, again suggesting slight differences in some memory‐processing mechanisms.…”
Section: Discussioncontrasting
confidence: 42%
“…Patients with MCI and dementia perform distinctly across these factors; thus, taking this performance into consideration could provide more accurate classification of cognitive function. A recent study tested the newly developed visual CVLT‐II protocol and found it comparable with the standard CVLT‐II protocol . This study also found overwhelming performance similarities on the visual CVLT‐II among a sample of experienced CI users and older NH adults with the exception of recency recall deficits, proactive interference, and forgetting, again suggesting slight differences in some memory‐processing mechanisms.…”
Section: Discussioncontrasting
confidence: 42%
“…In this study, we compared long-term prelingually deaf CI users with NH controls who were comparable in age and nonverbal IQ. Our sample of CI users differs from the earlier samples studied by Heydebrand et al (2007), Holden et al (2013), and Pisoni et al (2018), which consisted of postlingually deaf adult CI users who had an early period of typical development when they had sufficient hearing to acquire spoken language normally. In addition, Heydebrand et al and Holden et al used a global aggregate measure of verbal memory derived from the CVLT-II, whereas the current study focused on specific CVLT-II measures in order to understand the differential contributions of specific component subprocesses of verbal learning and memory.…”
Section: Discussionmentioning
confidence: 88%
“…Previous research suggested important contributions of downstream cognitive processing (i.e., information processing following initial perception and encoding) as one of the factors underlying the enormous variability and individual differences observed in speech and language outcomes after implantation. However, except for a few exceptions (Heydebrand et al, 2007;Holden et al, 2013;Pisoni et al, 2018), almost all previous studies of verbal memory in this clinical population have been primarily focused on short-term and working memory using rote memory span measures. Other core aspects of memory such as verbal learning, self-generated organizational strategies, encoding and retrieval interactions, and measures of retention in long-term memory have not been studied by researchers working with this clinical population.…”
Section: Discussionmentioning
confidence: 99%
“…Speed of phonological and lexical access were assessed using the Test of Word Reading Efficiency, version 2. Lastly, verbal learning and memory were assessed using the California Verbal Learning Test, version II . Details regarding these tests are described in Appendix A.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, verbal learning and memory were assessed using the California Verbal Learning Test, version II. 20,21 Details regarding these tests are described in Appendix A.…”
Section: Methodsmentioning
confidence: 99%